1979
DOI: 10.1051/jphys:01979004006056300
|View full text |Cite
|
Sign up to set email alerts
|

Rotational motion in plastic quinuclidine : Results from quasielastic neutron scattering

Abstract: Results of incoherent quasielastic neutron scattering experiments on quinuclidine, C7Hl3N, in its plastic phase (room temperature) are presented. The observed quasielastic spectra are compared to several models for the rotational motion of the molecules. It is found that the data support a picture, where the molecules perform 90°-reorientations about crystallographic C4-axes with a residence time of (24.8 ± 2.5).10-12 s, and 120°-reorientations about the molecular C3-axis with a residence time of (9.6 ± 2.0). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
0

Year Published

1979
1979
1986
1986

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…Finally, the reorientational molecular motion in the plastic phase of BCO seems rather similar to that observed in l-azabicyclo[2.2.2]octane [ABCO]. In that compound, both quasi-elastic neutron scattering [25] and n.m.r. 14N and 1 H relaxation time measurements [26] were able to distinguish between two reorientational motions and each concluded that C3 reorientation was faster than the 900 jumps by factors 2.6 and 4.2 respectively at room temperature.…”
supporting
confidence: 65%
“…Finally, the reorientational molecular motion in the plastic phase of BCO seems rather similar to that observed in l-azabicyclo[2.2.2]octane [ABCO]. In that compound, both quasi-elastic neutron scattering [25] and n.m.r. 14N and 1 H relaxation time measurements [26] were able to distinguish between two reorientational motions and each concluded that C3 reorientation was faster than the 900 jumps by factors 2.6 and 4.2 respectively at room temperature.…”
supporting
confidence: 65%
“…The present analysis, based on single crystal X-ray diffraction, was undertaken to provide a structural basis to related investigations on the dynamics of disorder in the plastic phase of quinuclidine [7,8].…”
mentioning
confidence: 99%
“…13C relaxation times in the disordered phases of these molecules reflect a high degree of anisotropy, but we were unable to obtain a consistent account of the T , ratios in terms of Woessner's two-parameter rotational diffusion model (13). Perhaps anisotropic jump models along the lines of those used by Brot and co-workers (14) in the analysis of neutron scattering and nmr data for disordered quinuclidine, HC(CH,CH,),N, will prove to be useful in this regard, but many more experiments are needed.…”
mentioning
confidence: 81%